Elimination of E. Faecalis by a New Non‐Thermal Atmospheric Pressure Plasma Handheld Device for Endodontic Treatment. A Preliminary Investigation1. Issue 6 (19th March 2013) - Jablonowski, Lukasz; Koban, Ina; Berg, Marie H.; Kindel, Eckhard; Duske, Kathrin; Schröder, Karsten; Weltmann, Klaus‐Dieter; Kocher, Thomas
Abstract The aim of this study was to investigate the feasibility of an atmospheric pressure plasma jet (PJ) for endodontic treatment and to compare the antimicrobial efficiency with conventional irrigation solutions (chlorhexidine digluconate (CHX), sodium hypochlorite (NaOCl)) against intracanal bacteria (E. faecalis) using a standardized simulated root canal model. The disinfection efficiency was determined by number of colony forming units. Scanning electron microscopy was used to investigate the effect of the treatment procedures on bacteria inside the root canal. The PJ achieved a significantly higher microbial reduction than chemical CHX irrigation and a comparable one with NaOCl. The application of PJ for endodontic treatment could provide a new possibility of controlling endodontic infection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>